Glutamate enhances shrimp antibacterial ability by boosting its cellular immunity - Lei Ma; Wenyong Jiang; Zhiyao Lu; Yanmei Tong; Qingyun Liu; Zhonghua He; Xiuli Chen; Yongzhen Zhao; Fan Wang (Comparative Immunology Reports)
Glutamate has been widely used in the feed industry to promote animal growth and enhance meat quality. However, its application in crustacean aquaculture remains relatively underexplored. In this study, we demonstrate a correlation between plasma glutamate increased the total hemocyte counts in shrimp within two hours, an effect that was reversed by co-injection with a Grik2 inhibitor. Subsequent feeding trials showed that incorporating 0.25 % glutamate into shrimp diets significantly raised the glutamate concentration in muscle tissue, resulting in a 7 % increase in glutamate content. Moreover, feeding experiments combined with differential transcriptome analysis revealed that shrimp fed a diet supplemented with 0.25 % glutamate exhibited enhanced resistance to Vibrio infections, likely through the upregulation of immune-related genes. These findings suggest that glutamate not only improves the anti-Vibrio defenses of shrimp but also enhances their flavor profile. Therefore, glutamate could serve as a beneficial feed supplement to promote disease resistance in shrimp aquaculture.